Tetrapyrrole biosynthetic enzyme protoporphyrinogen IX oxidase 1 is required for plastid RNA editing - Zhang, Fan; Tang, Weijiang; Hedtke, Boris; Zhong, Linlin; Liu, Lin; Peng, Lianwei; Lu, Congming; Grimm, Bernhard; Lin, Rongcheng (Proceedings of the National Academy of Sciences - PNAS, 2014)
RNA editing is a posttranscriptional process that covalently alters the sequence of RNA molecules and plays important biological roles in both animals and land plants. In flowering plants, RNA editing converts specific cytidine residues to uridine in both plastid and mitochondrial transcripts. Previous studies identified pentatricopeptide repeat (PPR) motif-containing proteins as site-specific recognition factors for cytidine targets in RNA sequences. However, the regulatory mechanism underlying RNA editing was largely unknown. Here, we report that protoporphyrinogen IX oxidase 1 (PPO1), an enzyme that catalyzes protoporphyrinogen IX into protoporphyrin IX in the tetrapyrrole biosynthetic pathway, plays an unexpected role in editing multiple sites of plastid RNA transcripts, most of which encode subunits of the NADH dehydrogenase-like complex (NDH), in the reference plant Arabidopsis thaliana. We identified multiple organellar RNA editing factors (MORFs), including MORF2, MORF8, and MORF9, that interact with PPO1. We found that two conserved motifs within the 22-aa region at the N terminus of PPO1 are essential for its interaction with MORFs, its RNA editing function, and subsequently, its effect on NDH activity. However, transgenic plants lacking key domains for the tetrapyrrole biosynthetic activity of PPO1 exhibit normal RNA editing. Furthermore, MORF2 and MORF9 interact with three PPRs or related proteins required for editing of ndhB and ndhD sites. These results reveal that the tetrapyrrole biosynthetic enzyme PPO1 is required for plastid RNA editing, acting as a regulator that promotes the stability of MORF proteins through physical interaction.